Effect of transition on QOL among Chinese children who underwent liver transplantation more than 5 years earlier† - Lu Ye-Feng; Zhou Tao; Xi Hui-Qin; Xia Qiang (Sciendo, 2023)
This study was conducted to test the effect of transition on the quality of life (QOL) among Chinese children who underwent liver transplantation more than 5 years earlier.